The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1017/s1751731114001256
|View full text |Cite
|
Sign up to set email alerts
|

Reference values for biochemical parameters in blood serum of young and adult alpacas (Vicugna pacos)

Abstract: The aim of this study was to establish reference interval for biochemical parameters in blood of alpacas on the basis of large population of clinically healthy animals, and to determine the influence of sex, age and season on nitrogen and lipid metabolites, enzymes, electrolytes, vitamins and minerals in blood of alpacas. Blood samples were collected from 311 alpacas (61 males and 201 females > 6 months of age and 49 crias (21 males and 28 females) ⩽ 6 months of age). Selected farms were located in Central Eur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
11
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 17 publications
5
11
0
4
Order By: Relevance
“…Range values from live animals are in accordance with Hengrave Burri et al, [3], Dawson et al, [4], and Husakova et al, [5]. Unfortunately, no reference range values regarding dead animals are available.…”
Section: Case Presentationsupporting
confidence: 82%
“…Range values from live animals are in accordance with Hengrave Burri et al, [3], Dawson et al, [4], and Husakova et al, [5]. Unfortunately, no reference range values regarding dead animals are available.…”
Section: Case Presentationsupporting
confidence: 82%
“…The mean concentrations of retinol in serum of alpacas in the present study are comparable to those reported in adult alpacas bred in Central Europe (Husakova et al., ) and are consistent with the reference interval for retinol in serum of alpacas (Foster et al., ). Such reference interval for retinol is not available for llamas.…”
Section: Concentrations Of Carotenoids Retinol (Vitamin A) and α‐Tocsupporting
confidence: 92%
“…By contrast, Husakova et al. () found no influence of sex on serum retinol and α ‐tocopherol concentrations in alpacas, but seasonal effects with higher concentrations of retinol and α ‐tocopherol during the winter feeding period, which could be explained by the increased usage of vitamin–mineral supplements by alpaca breeders. The effects of dietary supplementation, age or parturition on plasma retinol and α ‐tocopherol concentrations are also described in other herbivores such as dairy cows, pre‐ruminant calves or mares (Nonnecke et al., ; Schweigert and Gottwald, ; Calderon et al., ).…”
Section: Concentrations Of Carotenoids Retinol (Vitamin A) and α‐Tocmentioning
confidence: 92%
“…Pregnancy diagnosis was carried out at the end of the breeding period. in alpacas from to Central Europe farms (Husakova et al 2014). Indeed, the non-pregnant group slightly exceeded this range.…”
Section: Resultsmentioning
confidence: 84%